Polar Cod in a Changing Arctic. Toxicity of crude oil on sensitive life history stages of a key Arctic species - Bender, Morgan Lizabeth (Marine Environmental Research, 2020)
Environmental change in the Arctic is occurring at an unprecedented rate with a loss of sea ice and warmer sea temperatures, simultaneously as increased human activity in the Arctic poses a risk of petroleum pollution. The potential future of a key Arctic forage fish, polar cod ( Boreogadus saida ), was investigated using laboratory simulations of oil spills during sensitive life-history stages: maturation, post-spawning, and early life stages. I hypothesized that exposure to crude oil would result in adverse effects on individual fitness during these sensitive life-history stages. Changes in growth, metabolism, reproduction, and survival were followed to provide an integrated response to determine the risk to individual fitness to deliver more robust predictions for effects at the population and ecological levels. Findings reveal the physiological robustness of mature stages of polar cod chronically exposed to low levels (post-spill concentrations) or acutely to high (present-spill) crude oil concentrations. Effects observed on sperm motility under dietary exposure and gonadal development in females exposed to burned oil residues, an oil spill response action, require follow-up examination, especially in light of the importance of gamete quality to individual fitness. Reduced energy reserves and condition in the post-spawning stage suggests increased physiological sensitivity of this life-history stage. The high sensitivity of eggs and larvae to low levels of crude oil was further amplified by a 2.3°C increase in water temperature. The interactive effects of warmer water and low levels of petroleum pollution demonstrate the vulnerability of polar cod early life stages. Determining how the sentinel species, polar cod, will respond to these environmental and ecological stressors and what influence this will have on the resilience of the Arctic marine ecosystem is the future aim of this research.